57.3k views
2 votes
6-3(x-5)=5x-11 how do i do this

User Yakhyo
by
5.2k points

2 Answers

3 votes

Expand

6 - 3x + 15 = 5x - 11

Simplify 6 - 3x + 15 to -3x + 21

-3x + 21 = 5x - 11

Add 3x to both sides

21 = 5x - 11 + 3x

Simplify 5x - 11 + 3x to 8x - 11

21 = 8x - 11

Add 11 to both sides

21 + 11 = 8x

Simplify 21 + 11 to 32

32 = 8x

Divide both sides by 8

32/8 = x

Simplify 32/8 to 4

4 = x

Switch sides

x = 4

User Kourtney
by
5.8k points
2 votes

Answer:

4=x

Explanation:

6-3(x-5)=5x-11

Distribute the -3

6 -3x +15 = 5x -11

Combine like terms

21 -3x = 5x-11

Add 3x to each side

21-3x+3x = 5x+3x-11

21 = 8x-11

Add 11 to each side

21+11 = 8x-11+11

32 = 8x

Divide by 8

32/8 = 8x/8

4 =x

User Steve Schmitt
by
5.7k points